2014 IEEE 5th International Symposium on Power Electronics for Distributed Generation Systems (PEDG) 2014
DOI: 10.1109/pedg.2014.6878702
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy logic based frequency control by V2G aggregators

Abstract: This paper presents a fuzzy based frequency control strategy by the aggregator based plug-in electric vehicles (PEVs). The frequency control is proposed from the view point of the frequency instability which possibly caused by the distribution level PV power penetration and load demand variation as well as uncontrolled charging and discharging of PEVs. Two fuzzy logic controllers (FLCs) have been developed, one as charging station controller and another as vehicle-to-grid (V2G) controller, to provide frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…These rules are achieved logic and analysis. Fuzzy rule i in this controller is expressed as follows [19]: Rule i: IF f ∆ is L x and SOC is M y , THEN P I is Z l x= 1,2, … , 7, y=1,2, …,5 , l=1,2,3,…,9…”
Section: Design Of Controllermentioning
confidence: 99%
“…These rules are achieved logic and analysis. Fuzzy rule i in this controller is expressed as follows [19]: Rule i: IF f ∆ is L x and SOC is M y , THEN P I is Z l x= 1,2, … , 7, y=1,2, …,5 , l=1,2,3,…,9…”
Section: Design Of Controllermentioning
confidence: 99%
“…In addition to the more traditional approaches, the various proposed methods have utilized soft computing solutions. A fuzzy logic based frequency control method was developed by Datta (Datta, 2014), where electric vehicle charging was controlled to provide frequency regulation. Similar fuzzy methods were also utilized for photovoltaics inverter control (Datta and Senjyu, 2013).…”
Section: Controlling (Via) Frequencymentioning
confidence: 99%
“…Furthermore, the work done in [20] proposed a method for primary frequency control (PFC) using a simple constant droop characteristic, implemented in an isolated network model with a conventional generator and inertial emulation. Some other studies [21,22] suggested a better approach for frequency control, using fuzzy logic. The fuzzy controller receives information from PEV batteries and the grid, such as SOC and frequency deviation, controlling the output power in a more efficient and effective fashion.…”
Section: Introductionmentioning
confidence: 99%